42+y=7y

Simple and best practice solution for 42+y=7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42+y=7y equation:



42+y=7y
We move all terms to the left:
42+y-(7y)=0
We add all the numbers together, and all the variables
-6y+42=0
We move all terms containing y to the left, all other terms to the right
-6y=-42
y=-42/-6
y=+7

See similar equations:

| -10v=-80 | | -6=1/4x+6 | | 2z+3=6 | | 16+7s=65 | | 152r=1064 | | 143=-13a | | 5x=62-17 | | 3y+5=6+2y | | 103h=7(72−73h)−103, | | 15+2=10x+7 | | 1/5(x+1/2)=-1/2 | | b+22/9=4 | | 3x-41=-8 | | 8a=-160 | | 4x^2+4x+48=0 | | 5=3/2x+6 | | u+39=-7 | | 5m-38=37 | | x+5.5=-10.5 | | -7x-8=−10x+4 | | –9x+16=–5x | | p/4-2=6 | | 2x-24=8x+12 | | 180-x=35x | | 7q-12=9 | | –4g+26=9g | | x*3=2.4 | | 5r-2=6r=5= | | 8y=-10+3y | | 55=-25+x | | 2.1x-3.5=1.1x-4 | | 12h=+5 |

Equations solver categories